The experimental chemical hardness in the interaction between β-tubulin and epothilone B - Corzo, S. P.; Bueno, P. R. [UNESP]; Miranda, D. A. (IOP Publishing, 2019)
We showed the use of the experimental chemical hardness in the analysis of the interaction between β-tubulin and epothilone B. The interaction is analyzed by exposing the Epothilone B to a sensor based on an organic self-assembled monolayer functionalized with Beta tubulin. The proposed methodology is nondestructive and label-free. It allows us to compare the interaction between Beta-tubulin and different concentrations of the pharmacological molecule, i.e., epothilone B. The interaction is analyzed by the experimental hardness obtained according to the Miranda-Bueno methodology. We observed a linear behavior between the logarithm of the chemical hardness and the logarithm of epothilone B concentration. The results suggest the experimental chemical hardness can be used to compare the interaction of β-tubulin with epothilone B and with other pharmacological molecules.